Mortality rates, life expectancy, and causes of death in people with hemophilia A or B in the United Kingdom who were not infected with HIV. - Darby, S; Kan, S; Spooner, R; Giangrande, P; Hill, F; Hay, C; Lee, C; Ludlam, C; Williams, M (2007)
Since the 1970s, mortality in the hemophilia population has been dominated by human immunodeficiency virus (HIV) and few reports have described mortality in uninfected individuals. This study presents mortality in 6018 people with hemophilia A or B in the United Kingdom during 1977 to 1998 who were not infected with HIV, with follow-up until January 1, 2000. Given disease severity and factor inhibitor status, all-cause mortality did not differ significantly between hemophilia A and hemophilia B. In severe hemophilia, all-cause mortality did not change significantly during 1977 to 1999. During this period, it exceeded mortality in the general population by a factor of 2.69 (95% confidence interval [CI]: 2.37-3.05), and median life expectancy in severe hemophilia was 63 years. In moderate/mild hemophilia, all-cause mortality did not change significantly during 1985 to 1999, and median life expectancy was 75 years. Compared with mortality in the general population, mortality from bleeding and its consequences, and from liver diseases and Hodgkin disease, was increased, but for ischemic heart disease it was lower, at only 62% (95% CI: 51%-76%) of general population rates, and for 14 other specific causes it did not differ significantly from general population rates. There was no evidence of any death from variant Creutzfeldt-Jakob disease or from conditions that could be confused with it.